Internationalization process of Small Medium Enterprises (SMEs): A review paper - Nurshazani Fadli Salihin; Zuraidah Jamrin; Sidah Idris (Penerbit UMS, 2019)
Small Medium Enterprises (SMEs) has become an active role in the development of the economy for a country. It is not only giving an impact on the local market but also in the international market. The involvement of SME in the international market has brought a big contribution to economic development, employment, and a nation’s total export. Despite these contributions, SMEs inevitably are lack of resources, capability and market power as compared to the large firm. In Malaysia, the total establishment of SMEs is higher, the involvement of these SME into the international market is still considering low. This conceptual paper aims to examine previous scholar research papers related to the internationalization process of the SMEs that will enhance the conceptual understanding of the study. The internationalization is a process of increasing involvement in the international operation and the process of adopting the firm’s operations that consist of strategy, structure, and resources towards the international environment. This paper reviews the study and research that have been done by scholars on the internationalization process for SMEs in different economic level. Throughout the analysis, the study finds similar and different factors that play a role on the internationalization process, the classification of theory and method that have been used in the study from the finding of the previous studies. This review will give a better understanding of the field of internationalization process for the SMEs.